Technological Pedagogical Content Knowledge (TPACK) in Practice: Measuring Teachers’ Proficiency at Public and Private Universities of Lahore, Pakistan (Journal of Asian Development Studies, 2023)
This study addresses the critical issue of Technological Pedagogical Content Knowledge (TPACK) implementation among teachers at public and private universities in Lahore, Pakistan. In an era marked by rapid advancements in Information and Communication Technology (ICT), it becomes imperative to assess the readiness of educators to leverage these tools effectively. The research identifies a profound gap in current teaching practices, where teachers. However, well-versed in subject matter knowledge often needs more pedagogical skills and technological proficiency to harness the full potential of ICT for meaningful content delivery. The study involved 48 teachers from Information and Technology and Business Schools faculties across four universities (two private and two public). Utilizing a survey questionnaire with 82 closed-ended items, advanced statistical techniques like Pearson product-moment correlation analysis and multiple linear regression were employed to answer key research questions. Findings reveal strong correlations between various TPACK factors, emphasizing the interconnectedness of pedagogical knowledge, content knowledge, and technological competence. In light of these findings, policy recommendations include requiring higher education institutions to prioritize professional development opportunities, encouraging collaborative learning among faculty, and revisiting curriculum designs to incorporate TPACK principles. Furthermore, ensuring robust technology infrastructure, facilitating ongoing assessments of technology integration's impact, and fostering a culture of continuous improvement are essential steps in bridging the TPACK proficiency gap among educators. The study underscores the importance of equipping teachers with the necessary skills to navigate the evolving landscape of education, ultimately leading to more effective pedagogy and content delivery in higher education settings in Lahore, Pakistan.